Najwa Shihab’s Attitudes in Narasi TV Forming Resistant Discourse to House of Representatives’ Members - Ratnasari, Desy; Marta, Rustono Farady; Pangabean, Hana (Jurnal Ilmiah Peuradeun, 2021)
Each Policy and Performance made by the central government and the Republic of Indonesian House of Representatives will surely attract people’s attention and responses as one responded by Najwa Shihab through a video addressed to the honorable Mister and Mistress House of Representatives members in Narasi TV. This research employed a descriptive-interpretative approach using the theory of Elaboration Likelihood Model and Critical Discourse Analysis method implemented in three analytical phases to study Najwa Shihab’s argumentations and attitudes. The results showed that Najwa Shihab expressed her insights on social relations and identities which were unequal between her and House of Representatives members. The discourse builds her supremacies, thoughts, and ideas to legitimate herself as a people’s representative, directing people’s opinions through argumentations, self-values, and attitudes that tended to be resistant to the House of Representatives members.